Adolescents' neural reactivity to acute psychosocial stress: dysfunctional regulation habits are linked to temporal gyrus response. (9th February 2023) - Golde, Sabrina; Gleich, Tobias; Romund, Lydia; Stippl, Anna; Pelz, Patricia; Raufelder, Diana; Lorenz, Robert C.; Beck, Anne
Abstract: Mid-adolescence is a critical time for the development of stress-related disorders and it is associated with significant social vulnerability. However, little is known about normative neural processes accompanying psychosocial stress at this time. Previous research found that emotion regulation strategies critically influence the relationship between stress and the development of psychiatric symptoms during adolescence. Using functional magnetic resonance imaging (fMRI), we examined neural responses to acute stress and analyzed whether the tendency to use adaptive or maladaptive emotion regulation strategies is related to neural and autonomic stress responses. Results show large linear activation increases from low to medium to high stress levels mainly in medial prefrontal, insulae and temporal areas. Caudate and subgenual anterior cingulate cortex, neural areas related to reward and affective valuations, showed linearly decreasing activation. In line with our hypothesis, the current adolescent neural stress profile resembled social rejection and was characterized by pronounced activation in insula, angular and temporal cortices. Moreover, results point to an intriguing role of the anterior temporal gyrus. Stress-related activity in the anterior temporal gyrus was positively related to maladaptive regulation strategies and stress-induced autonomic activity. Maladaptive coping might increase the social threat and reappraisal load of a stressor, relating to higher stress sensitivity of anterior temporal cortices.